Performance management : perspectives on employee performance - Williams, Richard S. (International Thomson Business Press, 1998)
What is performance management? The organizational context I, II. Individual performance I, II III. Reviewing and supporting performance. Rewarding performance. Developing and designing performance management. Implementing and managing performance management.